Сучасні реформи у галузі вищої освіти: досвід європейських країн - Заячук, Юлія (Studies in Comparative Education, 2013)
Статтю присвячено вивченню процесу сучасних європейських реформ у галузі вищої освіти. Порівняльний аналіз цих реформ та процесу їхнього упровадження різними європейськими країнами здійснюється з урахуванням історичних освітніх традицій та сучасних економічних умов на прикладі систем вищої освіти Німеччини, Фінляндії та України. У статті також проаналізовано зміни умов діяльності та «виклики» для професії університетського викладача в умовах Болонської реформи. Статья посвящена изучению процесса современных европейских реформ в области высшего образования. Сравнительный анализ этих реформ и процесса их внедрения различными европейскими странами осуществляется с учетом исторических образовательных традиций и современных экономических условий на примере систем высшего образования Германии, Финляндии и Украины. В статье также проанализированы изменения условий деятельности и «вызовы» для профессии университетского преподавателя в условиях Болонской реформы. This article presents the results of the recent research in the area of European higher education reforms obtained between September 2011 and February 2012 in Humboldt University in Berlin, Germany, and the University of Turku, Finland supported by EMECW Program. The implemented methodological approach is based on the questionnaires, meetings, and interviews with different actors involved in the University system at different levels – with professors, scientists, PhD, Master and Bachelor students and administrators dealing with student affairs. The emphasis in this article is made on the issue of contemporary processes of reforming of higher education system by the example of different European countries and different European higher education models, such as Humboldtian (Germany) and Nordic (Finland). Comparative analysis of current European higher education reforms and adoption of them by different countries considering historic educational backgrounds and present conditions of European educational integration by the example of the University systems of Germany, Finland, and Ukraine has been done. A special emphasis in the article is done on the research of capabilities, challenges and the unsolved problems of Bologna reforms by the example of implementation of core objectives of Bologna reforms, like mobility, employability, attractiveness, credit accumulation in certain European universities. Other emphasizes is done on both purposes of Bologna reform: restructuring of higher education and having a different composition of competences; and internationalization of higher education and mobility. Changing conditions and challenges of academic profession in different European countries with Bologna reforms are considered in this article as well. In this context, comparative analysis of differences between European countries are presented considering such points as limitation of study time and structuring of curriculum; as well as individual and institutional components of academic freedom of Professor community under current higher education reform.